KAJIAN KUALITAS PEMBAKARAN TERHADAP PENGGUNAAN FILTER BBM PADA MESIN DIESEL - Tatun Hayatun Nufus; Ariek Sulistyowati; Asep Yana; Fitri Wijayanti (Politeknik Negeri Jakarta, 2019)
The price of oil fuel continues to rise, decreased supplies oil at the other side, those two factors motivate researchers to conduct research related to the efficient use of fuel. Have been made three types of fuel oil which the principle of an electromagnet used a filter, all three made of the coil with a convolution wire as many as 5000 a convolution and diameter of the nucleus of a coil 44.5 mm, 28.5 mm and 17.5 mm, a filter tested in a diesel engine. Testing done in the rpm the ignition is started 1100 until 1700 rpm, by opening throttle % to 60 % from 30%. Testing first one was done by making constant round of 1500 rpm and openings throttle vary from 30 % to 60%, next testing done with the variation of rpm start 1100 rpm until 1700 rpm by making constant valve as 40 % and of 60 % . The purpose of the variations to obtain optimum result against consumption of material fuel ( sfc ) the most little uses. Testing was done in a laboratory material.